Pendampingan Manajemen Organisasi Kepanduan Hizbul Wathan dalam Meningkatkan Tata Kelola Organisasi Kwartir Daerah Kabupaten Ngawi Tahun 2025 - Sumarno Sumarno (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2025)
This Community Service Activity (PKM) aims to increase the organizational management capacity of the Hizbul Wathan Scout Scout Ngawi Regency through assistance in the preparation of organizational documents, strengthening the administrative system, planning work programs, improving management competencies, and developing an organizational evaluation system. The implementation method uses a Participatory Action Research (PAR) approach combined with training, workshops, Focus Group Discussions (FGD), consultation, intensive mentoring, monitoring, and evaluation. The results of the activity show that mentoring is able to increase management's understanding of organizational functions, improve the quarterly administration system, produce more systematic organizational planning documents, improve coordination between management, and strengthen organizational governance in a sustainable manner. In addition, this activity produces various outputs in the form of organizational administrative guidelines, annual work programs, monitoring and evaluation instruments, and increasing the competence of the management in carrying out organizational functions. This mentoring program has a positive impact on increasing the effectiveness of the Hizbul Wathan Scouting organization in Ngawi Regency so that it is expected to become a model for fostering scouting organizations that can be replicated in other regional quarters.